Integrated infrastructure-plan analysis for resilience enhancement of post-hazards access to critical facilities. (October 2021) - Dong, Shangjia; Malecha, Matthew; Farahmand, Hamed; Mostafavi, Ali; Berke, Philip R.; Woodruff, Sierra C.
Abstract: This paper presents an integrated infrastructure-policy framework to analyze policy attention on addressing road infrastructure network vulnerability in terms of accessing critical facilities in the aftermath of a flood. Coping with network vulnerability, particularly physical access to various critical facilities and the services they provide, is an essential step in achieving a resilient community. However, the extent to which the network of local plans addresses such vulnerability remains unclear. To bridge this gap, this paper uses the Plan Integration for Resilience Scorecard method to examine the infrastructure-related policy attention in relation to community vulnerability vis-a-vis disrupted access to critical facilities. The proposed framework is tested in a set of super neighborhoods in Houston, Texas. Findings reveal a discrepancy between the policy effort and network vulnerability and identifies strengths and weaknesses of various plans in addressing disrupted access to critical facilities. The framework introduced in this paper provides a tool for stakeholders to evaluate an existing network of plans and identify gaps for future resilience improvement. Highlights: Network analysis reveals disparities in community post-disaster access to critical facilities. Resilience scorecard method can help examine the infrastructure-related policy attention. Analysis show that policy scores do not target vulnerable districts with low critical facility access. This paper enables an infrastructure-plan integration analysis framework.